Maqashid al-Shariah sebagai Solusi atas Problematika Kontemporer Ibadah Kurban - Rachmad Saleh Nasution (Prodi Ekonomi Syariah, Fakultas Syariah dan Hukum, Universitas PTIQ Jakarta, 2024)
The practice of Qurban (animal sacrifice) is one of the significant rituals in Islam, carrying deep spiritual and social values. However, its implementation on the ground often faces various technical, social, economic, and legal challenges that affect its effectiveness and overall benefit. This paper comprehensively examines the jurisprudential aspects of Qurban, the emerging contemporary issues, and practical solutions based on the approaches of maqashid al-shariah and contextual fiqh. The study highlights that technical problems such as the lack of qualified slaughterers and inadequate slaughtering facilities, as well as socio-economic issues like unequal meat distribution and low public awareness, are among the main challenges. Additionally, differences in fatwas among Islamic institutions and the lack of clear legal regulations contribute to confusion and potential misuse in Qurban practices. Proposed solutions include improving slaughter training programs, utilizing technology for transparent distribution, enhancing public education, and harmonizing fatwas from Islamic bodies such as MUI, NU, and Muhammadiyah to better meet the needs of both urban and rural communities. The maqashid al-shariah approach serves as the primary framework in formulating solutions that are not only compliant with Islamic law but also offer broad and sustainable social and economic benefits. This paper aims to serve as a reference for scholars, practitioners, and policymakers in optimizing the implementation of Qurban in the modern era.